1999
DOI: 10.1577/1548-8659(1999)128<0769:ifinul>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Introduced Fish in Northeastern USA Lakes: Regional Extent, Dominance, and Effect on Native Species Richness

Abstract: We assessed the effects of nonnative fish on native fish biodiversity, using assemblage data collected during 1991-1996 from 203 randomly selected lakes in the northeastern USA by the Environmental Monitoring and Assessment Program (EMAP) of the U.S. Environmental Protection Agency. An estimated 74% (Ϯ17.6%, 95% confidence interval) of the region's 10,608 lakes between 1 and 10,000 ha contain at least one introduced species. Based on our samples, nonnative individuals outnumbered natives in an estimated 31.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 20 publications
0
70
0
2
Order By: Relevance
“…Introduced largemouth bass have altered native fish communities, lowering both the species richness and abundance of native fish because of predation (Whitter and Kincaid 1999;Takahashi et al 2001;Azuma and Motomura 1998;Yonekura et al 2003;Jang et al 2006).…”
mentioning
confidence: 99%
“…Introduced largemouth bass have altered native fish communities, lowering both the species richness and abundance of native fish because of predation (Whitter and Kincaid 1999;Takahashi et al 2001;Azuma and Motomura 1998;Yonekura et al 2003;Jang et al 2006).…”
mentioning
confidence: 99%
“…They were first introduced into Japan during the late 19th to early 20th century from the United States (Azuma 1992;Yuma et al 1998). These exotic species can significantly affect the community structure of aquatic organisms through predation and competition for food, altering nutrient and energy flows in lentic ecosystems (Whittier and Kincaid 1999;Schindler and Scheuerell 2002;Maezono and Miyashita 2003). For instance, the location of largemouth bass at the top of the food-chain has driven some of the native fish populations to go extinct in a number of locales (Takamura 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Stream gradient is related to fish presence in other mountainous regions [e.g. Alaska (Hershey et al, 1999), Finland (Tonn et al, 1990)], and other studies in northeastern North America have shown negative correlation between lake altitude and native and introduced fish species richness (Whittier & Kincaid, 1999). In general, mountain lakes lacking fish tend to be located in small, high-altitude catchments and have basins Table 4 Predicted probabilities of current and historical fish absence in eastern and western model validation lakes.…”
Section: Western Lake Predictions and Model Assessmentmentioning
confidence: 98%